El Circo un Sueño que se volvió una profesión, historia de vida de David Ortiz Amaya (2023)
This work presents the story of David Ortiz Amaya, a circus artist and trainer in the municipality of Chía, through the narration of the main episodes that shaped the path he currently follows: the Circus. The focus of this qualitative research, using the Life History methodology, consisted of gathering information about David Ortiz's training process and artistic journey, focusing on two main categories: "Circus Artist and Clown" and "Clown Pedagogy and Juggling." It also aims to highlight the importance of life history in the academic context of the Circus and the relevance of Clown pedagogy and juggling in the training of new artists.